Analysis of Tonguing and Blowing Actions During Clarinet Performance - Pàmies-Vilà, Montserrat; Hofmann, Alex; Chatziioannou, Vasileios (Frontiers in Psychology, 2018)
Articulation on the clarinet is achieved by a combination of precise actions taking place inside the player's mouth. With the aim to analyse the effects of tonguing and blowing actions during playing, several physical variables are measured and parameters related to articulation are studied. Mouth pressure, mouthpiece pressure and reed displacement are recorded in an experiment with clarinet players to evaluate the influence of the player's actions on the selected parameters and on the sound. The results show that different combinations of tongue and blowing actions are used during performance. Portato and legato playing show constant blowing throughout the musical phrase, which varies according to the dynamic level. In portato, short tongue-reed interaction is used homogeneously among players and playing conditions. In staccato playing, where the tongue-reed contact is longer, the mouth pressure is reduced significantly between notes. Such a mouth-pressure decrease might be used to stop the note in slow staccato playing. It is hereby shown that when the note is stopped by the action of the tongue, not only the release transient but also the attack transient is shorter compared to the case where the vibration of the reed is stopped by a decrease of mouth pressure.